Security Dilemma dalam Ketegangan AS-Iran Pasca Serangan Kapal Tanker di Teluk Oman - Salsabila, Fenny Rizka; Yulianti, Dina (Jurnal ICMES, 2019)
This article aims to examine the tensions that occurred between the US and Iran, especially after the explosion of two tankers in the Gulf of Oman on June 13, 2019. The US accused Iran of being the perpetrators of the attack and took various actions in response, including increasing its military posture in the region. This article answers questions about the root of this tension in terms of the security dilemma concept of Booth and Wheeler (2008). The research was conducted qualitatively using data from mass media, documents, and journal articles. The findings of this research are that the US and Iran each interpret the other party as an enemy but the response given is different. The US gave a confrontational response by bringing forward its economic and military strength, while Iran in addition to giving signals (words) of resistance also gave a signal of reassurance or guarantee that it was prioritizing diplomacy and cooperation.